Semantic kernel SDK for intelligent applications - Williams, Trevoir (Packt Publishing, 2024)
Dive into the dynamic world of generative AI and learn to leverage Semantic Kernel SDK for real-world business applications. Begin by understanding the fundamentals of AI, large language models (LLMs), and the critical role of the Semantic Kernel in creating adaptive, intelligent systems. With a focus on practical use cases, you'll explore the potential of AI agents tailored for various business contexts. Progress through comprehensive hands-on modules that guide you through setting up your development environment, creating your first Semantic Kernel, and building AI applications. You'll master plugins, including time management and conversational tools, and learn to craft personalized AI agents using advanced prompt engineering techniques. Real-world examples ensure you gain the skills to apply this knowledge effectively. Conclude your journey with native function development, enabling seamless integration of custom business logic into your AI solutions. By course end, you'll have the expertise to build robust AI-driven applications that enhance productivity, decision-making, and user experiences. To access the supplementary materials, scroll down to the 'Resources' section above the 'Course Outline' and click 'Supplemental Content.' This will either initiate a download or redirect you to GitHub. What you will learn Understand the core principles of LLMs and Semantic Kernel Build AI agents tailored to business needs Create and customize plugins for specialized applications Develop native functions and integrate them with prompts Automate workflows with prompt engineering and function invocation Apply generative AI concepts to create intelligent, scalable solutions Audience This course is ideal for software developers, data analysts, AI enthusiasts, and technical professionals eager to harness the power of AI in business applications. It is well-suited for those with a foundational understanding of programming and familiarity with tools like Visual Studio or Azure. Beginners with a willingness to learn about AI concepts and hands-on integration will also benefit. About the Author Trevoir Williams: Trevoir Williams, a passionate software and system engineer from Jamaica, shares his extensive knowledge with students worldwide. Holding a Master's degree in Computer Science with a focus on Software Development and multiple Microsoft Azure Certifications, his educational background is robust. His diverse experience includes software consulting, engineering, database development, cloud systems, server administration, and lecturing, reflecting his commitment to technological excellence and education. He is also a talented musician, showcasing his versatility. He has penned works like Microservices Design Patterns in .NET and Azure Integration Guide for Business. His practical approach to teaching helps students grasp both theory and real-world applications.
Online resource; title from title details screen (O'Reilly, viewed December 30, 2024)
Keywords: Application software -- Development; Instructional films; Nonfiction films; Internet videos